Kajian Struktur Garap dan Estetika Sabet Kupu Tarung Pakeliran Jawatimuran Sajian Sareh Budi Utomo - Fani Dwi Nuriyanto; Suyanto Suyanto (Institut Seni Indonesia Surakarta, 2022)
This study reveals two problems related to the structure of the work and the aesthetics of the Sareh Budi Utomo sabet kupu tarung, including: (1) what is the structure of the work and the Sareh sabet kupu tarung? and (2) What is the aesthetic impression of the sabet kupu tarung that is presented by Sareh? These two problems were studied based on the sanggit garap and nuksma mungguh paradigms. Textual problems were analyzed using choreographic theory, aesthetic theory, and the concept of Javanese puppetry. This research is descriptive qualitative. Data were collected through literature study, interviews, and direct observation of the sabet kupu tarung wars served by Sareh Budi Utomo. The results showed: first, Sareh Budi Utomo had carried out the process of working on the structure of his sabet kupu tarung so that it had a different working structure sabet with the dalang in other sub styles. Second, the sabet kupu tarung of Sareh Budi Utomo created an aesthetic impression in the form of attractive, greget, semu, resik, trampil, rame, gayeng, nuksma and mungguh.